Structural and functional understanding of disease-associated mutations in V-ATPase subunit a1 and other isoforms - Indrawinata, Karen; Argiropoulos, Peter; Sugita, Shuzo (Frontiers in Molecular Neuroscience, 2023)
The vacuolar-type ATPase (V-ATPase) is a multisubunit protein composed of the cytosolic adenosine triphosphate (ATP) hydrolysis catalyzing V1 complex, and the integral membrane complex, Vo, responsible for proton translocation. The largest subunit of the Vo complex, subunit a, enables proton translocation upon ATP hydrolysis, mediated by the cytosolic V1 complex. Four known subunit a isoforms (a1–a4) are expressed in different cellular locations. Subunit a1 (also known as Voa1), the neural isoform, is strongly expressed in neurons and is encoded by the ATP6V0A1 gene. Global knockout of this gene in mice causes embryonic lethality, whereas pyramidal neuron-specific knockout resulted in neuronal cell death with impaired spatial and learning memory. Recently reported, de novo and biallelic mutations of the human ATP6V0A1 impair autophagic and lysosomal activities, contributing to neuronal cell death in developmental and epileptic encephalopathies (DEE) and early onset progressive myoclonus epilepsy (PME). The de novo heterozygous R740Q mutation is the most recurrent variant reported in cases of DEE. Homology studies suggest R740 deprotonates protons from specific glutamic acid residues in subunit c, highlighting its importance to the overall V-ATPase function. In this paper, we discuss the structure and mechanism of the V-ATPase, emphasizing how mutations in subunit a1 can lead to lysosomal and autophagic dysfunction in neurodevelopmental disorders, and how mutations to the non-neural isoforms, a2–a4, can also lead to various genetic diseases. Given the growing discovery of disease-causing variants of V-ATPase subunit a and its function as a pump-based regulator of intracellular organelle pH, this multiprotein complex warrants further investigation.